Morphogenesis and structure of Tifton 85 cultivated in subtropical climate and fertilized with nitrogen - Tiecher, Diego Daniel; Rocha, Marta Gomes da; Pötter, Luciana; Salvador, Paulo Roberto; Bergoli, Tuani Lopes; Milanesi, Gabriela Descovi (Acta Scientiarum. Animal Sciences, 2016)
The experiment evaluated the morphogenesis and structure of Tifton 85 (Cynodon spp.) cultivated in subtropical climate and fertilized with nitrogen (N). The experiment was a completely randomized design with four levels of N (Zero; 75; 150 or 225 kg ha-1) in nine replicates per area. The experimental animals were Suffolk female lambs. The grazing method was continuous to maintain the sward height at 15 cm ± 10%. The stem expansion increased by 0.000027 cm degree-days-1 to each kg N applied (linear model). According to nonlinear model, the highest stem expansion (0.0226 cm degree-days-1) was observed with the use 220.1 kg ha-1 N. The leaf lifespan fitted a linear regression model, with increase of 50 degree-days leaf -1, comparing the levels zero and 225 kg ha-1 of N. According to nonlinear regression model, the longest leaf lifespan (407.1 degree-days) was observed with the use 208.8 kg ha-1 N. With the maintenance of sward height at approximately 15 cm, we recommended to use 200 kg ha-1 N in Tifton 85 cultivated in subtropical climate.